Proof of Attribution of Property Interests in Personal Information in Constitutional Perspective - Zhanshan Hou (Studies in Law and Justice, 2024)
Personal information, as a component of big data, contains enormous economic value, and the storage, circulation and sharing of personal information in accordance with the law is also an inevitable requirement of the digital society. The basic condition for giving full play to the economic value of personal information is to clarify the attribution of the property rights and interests of personal information and to protect the legitimate interests of the subject of the rights. The attribution of property rights and interests in personal information should be defined on the basis of reasonable classification of personal information, taking into account the requirements of the socialist system, the goal of common prosperity, the system of distribution according to work and the promotion of economic development in the constitutional norms.